Otimização técnico-econômica e ambiental da cadeia de produção e do uso final do hidrogênio de origem renovável em Minas Gerais - Khalid, Halima (2025)
Renewable hydrogen has been consolidated as a key energy vector for decarbonizing emission- intensive sectors. This work addresses the technical, economic and environmental feasibility of hydrogen production. To this end, mixed integer linear programming (MILP) modeling was used, implemented in LINGO 20® software, considering capital investments, operating costs, raw material costs, transportation costs and associated emissions. The main economic indicators were analyzed, such as net present value (NPV), discounted payback and minimum sales price, in order to assess the risks and financial attractiveness of the projects. The study considered four technological routes for the production of renewable hydrogen: ethanol steam reforming (Ethanol_ESR), proton exchange membrane electrolysis (PEM_Electrolysis), biomethane reforming from vinasse (Vinasse_BD_SMR) and gasification of woody biomass (GS_WGS). In the first article, with an estimated demand of 57,751.76 t/year for the refining sector, the results indicated that the routes based on agro-industrial waste and biomass (GS_WGS and Vinasse_BD_SMR) were the most economically competitive, with an internal rate of return (IRR) of over 35%, payback of approximately 3 years and sales prices comparable to gray hydrogen. On the other hand, the Ethanol_ESR and PEM_Electrolysis routes presented greater financial challenges, with electrolysis being the most costly in terms of initial investment, with an IRR of 9% and a payback of 14 years. Ethanol_ESR, although with a lower investment, had its attractiveness reduced by the high cost of ethanol, resulting in a payback of 7 years. The sensitivity analysis showed that the waste-based routes were less vulnerable to market fluctuations. In the second article, aimed at producing renewable ammonia with a demand of 200,000 t/year, the results reinforced the critical influence of the choice of raw material on final costs. The Ethanol_ESR technology required the least investment (286 M$), but faced limitations due to the high cost of ethanol. On the other hand, the PEM_Eletrolise technology required the largest investment (645 M$) and showed the slowest return, with a payback of 8 years. The vinasse-based route (Vinasse_BD_SMR) stood out for having the lowest raw material cost and high environmental sustainability. GS_WGS, on the other hand, although economically viable, presented logistical obstacles related to the dispersal of biomass. The sensitivity analysis showed that the minimum sales price and the rate of return are decisive factors for financial viability, especially in scenarios with high operating costs. From an environmental point of view, both applications resulted in a negative balance of CO2 emissions, with significant reductions estimated at 462,000 tCO2eq/year in the refining sector and 580,000 tCO2eq/year in ammonia production, representing approximately 13% of total emissions from the nitrogen fertilizer sector in Brazil. These results reinforce the strategic role of renewable hydrogen in the transition to a low-carbon economy. It is concluded that the valorization of agro-industrial waste and the use of regional biomass, combined with logistical optimization and the support of public policies, are fundamental pillars for the technical and economic viability of sustainable production chains based on renewable hydrogen.